A new rooted tree optimization algorithm for economic dispatch with valve-point effect. (July 2016) - Labbi, Yacine; Attous, Djilani Ben; Gabbar, Hossam A.; Mahdad, Belkacem; Zidan, Aboelsood
Graphical abstract: Roots of plant behavior when they look for water (solution) (The search mechanism in RTO algorithm). Highlights: This paper presents RTO approach for solving the EDP with valve-point effect. Rooted tree optimization algorithm is a new meta-heuristic algorithm. It is a nature-based searching technique. The effectiveness of the proposed algorithm has been verified on different systems. Abstract: This work proposes a new optimization method called root tree optimization algorithm (RTO). The robustness and efficiency of the proposed RTO algorithm is validated on a 23 standard benchmark nonlinear functions and compared with well-known methods by addressing the same problem. Simulation results show effectiveness of the proposed RTO algorithm in term of solution quality and convergence characteristics. In order to evaluate the effectiveness of the proposed method, 3-unit, 30 Bus IEEE, 13-unit and 15-units are used as case studies with incremental fuel cost functions. The constraints include ramp rate limits, prohibited operating zones and the valve point effect. These constraints make the economic dispatch (ED) problem a non-convex minimization problem with constraints. Simulation results obtained by the proposed algorithm are compared with the results obtained using other methods available in the literature. Based on the numerical results, the proposed RTO algorithm is able to provide better solutions than other reported techniques in terms of fuel cost and robustness.